2003
DOI: 10.1007/s00442-003-1223-6
|View full text |Cite
|
Sign up to set email alerts
|

Parasite mediated mortality and host immune response explain age-related differences in blood parasitism in birds

Abstract: An important pattern in host-parasite assemblages is a higher intensity of parasites in juveniles than in adults, but the reasons for these differences remain obscure. Three non-mutually exclusive hypotheses have been proposed: (1) heavily parasitized juveniles die before being recruited into the adult population ('selection' hypothesis); (2) the development of an acquired immunity by the host in front of the parasite reduces the intensity of the parasite in adult hosts ('immunity' hypothesis); and (3) differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
3
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(157 citation statements)
references
References 24 publications
7
146
3
1
Order By: Relevance
“…The negative relationship between tuatara size and Ht prevalence contrasts with most other studies of reptilian blood parasites, which report that smaller or younger individuals were less likely to be infected with blood parasites because cumulative exposure to sources of infection increases with host age (Hepatozoon: Salkeld and Schwarzkopf, 2005;Plasmodium: Schall and Marghoob, 1995;Staats and Schall, 1996;haemogregarines: Sorci, 1996;Amo et al, 2004;Brown et al, 2006). However, the negative relationship between tuatara size and Ht intensity was consistent with numerous studies of reptilian blood parasites showing a decline in infection intensity of infected individuals with increased host size or age (Bromwich and Schall, 1986;Sol et al, 2003;Madsen et al, 2005;Brown et al, 2006) because younger individuals have had less opportunity to acquire immunity than older hosts (Hudson and Dobson, 1997;Sol et al, 2003).…”
Section: Host Size and Ht Infectionsupporting
confidence: 83%
See 2 more Smart Citations
“…The negative relationship between tuatara size and Ht prevalence contrasts with most other studies of reptilian blood parasites, which report that smaller or younger individuals were less likely to be infected with blood parasites because cumulative exposure to sources of infection increases with host age (Hepatozoon: Salkeld and Schwarzkopf, 2005;Plasmodium: Schall and Marghoob, 1995;Staats and Schall, 1996;haemogregarines: Sorci, 1996;Amo et al, 2004;Brown et al, 2006). However, the negative relationship between tuatara size and Ht intensity was consistent with numerous studies of reptilian blood parasites showing a decline in infection intensity of infected individuals with increased host size or age (Bromwich and Schall, 1986;Sol et al, 2003;Madsen et al, 2005;Brown et al, 2006) because younger individuals have had less opportunity to acquire immunity than older hosts (Hudson and Dobson, 1997;Sol et al, 2003).…”
Section: Host Size and Ht Infectionsupporting
confidence: 83%
“…Infection prevalence can vary with fluctuations in vector abundance, both seasonally (Bennett and Cameron, 1974) and spatially (Merila et al, 1995;Sol et al, 2000;Bajer et al, 2006), whereas patterns of infection within exposed populations can vary with host sex, body size, and reproductive status. The level of exposure to vectors can vary between host sexes if they differ in homerange size or activity rates (Krasnov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies from wild bird populations have shown that there are severe fitness costs associated with the acute phase of avian malaria (Richner et al 1995;Oppliger et al 1996;Atkinson et al 2001;Sol et al 2003). In the great tit (Parus major), females with Plasmodium malaria infections lay smaller egg clutches (Richner et al 1995;Oppliger et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, both the young and the adult cormorants are exposed to identical invasive forms of parasites occurring in their food. Consequently, the presence of most S. squamata in the immature birds is most likely a result of a much higher food uptake (related to high energy demand) by the immature birds during growth (Sitko, 1993) or the deficiency of their incompletely developed immunological system (Ros et al, 1997;Sol et al, 2003), or a combination of the two factors. However, effects of other environmental variables cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%